2002
DOI: 10.1055/s-0040-1715981
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Response, Middle Latency Response, and Late Cortical Evoked Potentials in Children with Learning Disabilities

Abstract: Auditory evoked potentials (AEPs) and behavioral tests were used to evaluate auditory processing in 10 children aged 7 to 11 years who were diagnosed as learning disabled (LD). AEPs included auditory brainstem responses (ABRs), middle latency responses (MLRs), and late cortical responses (P1, N1, P2, P3). Late cortical responses were recorded using an active listening oddball procedure. Auditory processing disorders were suspected in the LD children after a psychologist found phonologic processing and auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 81 publications
3
20
0
11
Order By: Relevance
“…Some studies have demonstrated different results when comparing click ABR results between normal children and those diagnosed with language disorders (i.e., lower amplitudes for waves I, III, and V compared with the control group) ( 19 ), learning difficulties (i.e., shorter latencies for wave V and interpeak III-V than the control group) ( 20 ), and specific language impairments (i.e., increased waves III and V latencies compared with the control group) ( 21 ). Among these findings, longer latencies and reduced wave amplitudes were more frequently observed.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated different results when comparing click ABR results between normal children and those diagnosed with language disorders (i.e., lower amplitudes for waves I, III, and V compared with the control group) ( 19 ), learning difficulties (i.e., shorter latencies for wave V and interpeak III-V than the control group) ( 20 ), and specific language impairments (i.e., increased waves III and V latencies compared with the control group) ( 21 ). Among these findings, longer latencies and reduced wave amplitudes were more frequently observed.…”
Section: Discussionmentioning
confidence: 99%
“…Longer latencies in speech‐evoked ABRs also have been observed in learning‐disabled subjects. 1 , 2 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Studies in typical reading children and adults have demonstrated that the precision with which the auditory brainstem encodes these temporal properties is significantly related to behavioral measures of speech perception (Anderson, Skoe, Chandrasekaran, Zecker, & Kraus, ; Hornickel, Chandrasekaran, Zecker, & Kraus, ; Hornickel, Skoe, Nicol, Zecker, & Kraus, ), phonological processing (White‐Schwoch & Kraus, ), and reading (Hornickel, Anderson, Skoe, Yi, & Kraus, ; Neef, Schaadt, & Friederici, ; Skoe, Brody, & Theodore, ). Accordingly, atypical auditory brainstem responses (ABRs) and frequency following responses (FFRs) have been found in individuals with a broad variety of learning problems (e.g., Cunningham, Nicol, Zecker, Bradlow, & Kraus, ; King et al, ; Purdy et al, ; Wible et al, ; Banai, ; Basu, Krishnan, & Weber‐Fox, ; Malayeri et al, ; for a review, see Banai, Abrams, & Kraus, ). Studies in individuals with exclusive reading‐based learning problems, that is, without comorbid‐specific language impairments or attention deficit disorders, are, however, limited.…”
Section: Introductionmentioning
confidence: 99%